Design for Maintainability of Basements and Wet Areas - Michael Yit Lin Chew (Buildings, 2021)
With the motto of “doing it right the first time”, this study focuses on spearheading the integration of designers, constructors, and facility mangers, at the outset of the planning/design stage, by providing easy-to-read tables summarising (1) knowledge learnt from past mistakes and (2) maintainability benchmarks, to ensure high maintainability for Basements and Wet Areas. The commonly occurring problems in Basements and Wet Areas of a total of 110 buildings comprising of commercial, hotels, industrial, institutions, healthcare facilities, and residential facilities were evaluated using case and field studies. Face-to-face interviews and workshops with the respective professionals involved in the design, construction, operation and maintenance (O&M) of the buildings were conducted for detailed investigation on each problem for their (a) problem types, (b) extent of problem, (c) failure mechanism, (d) good practices in design/construction/O&M/facilities management (FM), and (e) environmental issues. Easy-to-read tables of checklists based on a preventive/predictive performance-based approach, which defines acceptable standards in design, construction and O&M/FM practices, were derived. The checklists help enhance the integration of designers, constructors, and facilities managers (FM), ensuring high maintainability and productivity right at the outset of the planning/design stage. They also help professionals derive, customise, and validate their own Maintainable Design Appraisal System (MDAS) according to their own needs.